Evaluation of Sedative activity of Cannabis Sativa in mice (International Journal of Scientific Research and Management (IJSRM), 2024)
Background: Cannabis sativa Linn. (Family: Cannabaceae) is commonly cultivated in Bangladesh in moist areas such as riverbanks, lakes, canals, and roadsides. The leaves of this plant are traditionally used to treat insomnia, depression, and neurodegenerative diseases. Objective: The study’s objective is to investigate the sedative effects and phytochemical composition of the Cannabis sativa species in Nigeria. Methods: The elevated plus maze was used to assess the sedative effect of various fractions of aqueous methanol extracts of Cannabis sativa at a dosage of 100 mg/kg in mice. Comparisons were made between the sedative action of the extract and diazepam, which was used as the positive control. Additionally, acute toxicity was also evaluated during the assessment. Results: During the elevated plus-maze test, various parameters such as the number of entries in open arms and the number of entries in closed arms were recorded. The administration of different fractions of aqueous methanol extracts of Cannabis sativa resulted in a significant increase (p < 0.001) in the time spent in and the number of entries into open arms compared to the control group. Conclusion: The findings suggest that various concentrations of water-methanol extracts from Cannabis sativa exhibit sedative effects that are superior to those of the control (diazepam), supporting the use of this plant in traditional medicine. Further research should be conducted to investigate the active components of Cannabis sativa and understand the mechanism of its effects before proceeding to clinical trials.